On the throughput of a relay-assisted cognitive radio MIMO channel with space alignment - Sboui, Lokman; Ghazzai, Hakim; Rezki, Zouheir; Alouini, Mohamed-Slim (2014 12th International Symposium on Modeling and Optimization in Mobile, Ad Hoc, and Wireless Networks (WiOpt), 2014)
We study the achievable rate of a multiple antenna relay-assisted cognitive radio system where a secondary user (SU) aims to communicate instantaneously with the primary user (PU). A special linear precoding scheme is proposed to enable the SU to take advantage of the primary eigenmodes. The used eigenmodes are subject to an interference constraint fixed beforehand by the primary transmitter. Due to the absence of a direct link, both users exploit an amplify-and-forward relay to accomplish their transmissions to a common receiver. After decoding the PU signal, the receiver employs a successive interference cancellation (SIC) to estimate the secondary message. We derive the optimal power allocation that maximizes the achievable rate of the SU respecting interference, peak and relay power constraints. Furthermore, we analyze the SIC detection accuracy on the PU throughput. Numerical results highlight the cognitive rate gain achieved by our proposed scheme without harming the primary rate. In addition, we show that the relay has an important role in increasing or decreasing PU and SU rates especially when varying its power and/or its amplifying gain.